Two project players and a kilted kiwi with a granny from fife: (re)presenting Scotland at the 2015 Rugby World Cup. Issue 1 (2nd January 2020) - Cullen, John; Harris, John
Abstract: Research into the representation of national identities in international sport has developed markedly in the last 24 years. Much of this has focused on the print media portrayal of national identities in mega-events like the Olympic Games and the Football World Cup. This article looks at the ways in which rugby union players representing Scotland at the 2015 Rugby World Cup were portrayed across four newspapers during the 6 weeks of the tournament. It considers the ways in which national identities came into focus through newspaper narratives focusing on three members of the Scotland team who were born outside of that nation. This work highlights the contested terrain of the rules around player eligibility and broader notions of acceptance of these players as representatives of the Scottish nation.